Fronteira aberta: a construção social do poder de um potentado no Rio Grande de São Pedro (1750-1830) - Corrêa, Mariana Milbradt (2017)
The following work was developed in the concentration area of “History, Culture and Power” in the research line “Integration, Politics and Frontier” of the masters course of the Post Graduated Program in History from the Federal University of Santa Maria (UFSM), with support from CAPES scholarship. The goal is to enquire about forms of power’s social construction and apropriation of resources from the elites in an open frontier region in the end of the XVIII century and in the begin of XIX centuty. The study was elaborated from the trajectory analysis of a potentate located in Rio Grande de São Pedro, José de Abreu - Barão do Serro Largo. In this sense, we had thought about his role as a mediator, that adjusted to the local reality, was able to establish relations with the large and multi-ethnic population that inhabited the frontier, being one of the links connecting the region to the Portuguese administrative network. It was possible to perceive, therefore, that Abreu's social ascencion had been allowed by the opening of the frontier after the conquest of the Missions in 1801. The conquered territory opened spaces for the insertion of new elites, who took field’s possession and organized spaces of command in new frontier. Abreu constructed his military store from a series of factors, among which stood out the alliance with the indigenous local population (guaranis from the Missions and groups of charruas). Besides to the relationship with the groups of military and militiamen officers who went to that region, receiving land that was distributed by José de Abreu, in exchange, mainly, by the military services. It was also possible to verify, in the same way, that these groups were very integrated. Abreu also managed to establish close ties to the Court, which made possible his appointment to the position of Governor of Arms, and his projection to a command space within the province.